The Aesthetic Usage Response of Baju Kurung in Palembang City Government Tourism Office in Emphasizing Regional Identity - Chaniago, Efriyeni; Rohendi Rohidi, Tjetjep; Triyanto, Triyanto (Catharsis, 2020)
BajuKurung is a traditional dress of the Malay community in several countries namely Malaysia, Indonesia, Brunei Darussalam, and southern Thailand. The traditional clothes worn by Palembang women including in the form of bajukurung. In the development era of bajukurung replaced by modern clothes. The modification of bajukurung is now made according to the tastes of customers with a variety of shapes and accessories. This study aims to analyze the aesthetic response to the rules of wearing Palembang's traditional clothing in service in the form of patterns, motifs, textures, and colors of clothes worn by employees. Through this interdisciplinary approach by using qualitative method. The data is presented in the descriptive form. The object of study was the employee's bajukurung in Palembang Government Tourism office. The research data sources are primary and secondary data. The data collection techniques are conducted by observation, interview, and document study. The analysis procedure is conducted by data reduction, data presentation, and data verification. The analysis was conducted with the aesthetic formalism theory, the validity of the data by triangulation of data sources. The results showed that the aesthetic response of the employees was expressed through patterns, motifs, colors, and textures of the bajukurung material that were modified with the addition of beads, sequins, and ribbons. The aesthetic response of the user to the style modification of the kurung displays the beauty of clothes but does not eliminate the original form. Modifications to the clothes do not interferethe activities of the employees while working.